Effects of oral valganciclovir prophylaxis for cytomegalovirus infection in heart transplant patients - Dösch, Andreas; Repp, Janika; Hofmann, Nina; Erbel, Christian; Frankenstein, Lutz; Gleißner, Christian A.; Schmidt, Constanze; Ruhparwar, Arjang; Zugck, Christian; Schnitzler, Paul; Ehlermann, Philipp; Katus, Hugo (Drug design, development and therapy, 2012)
Background: Cytomegalovirus (CMV) infection is a serious complication following heart transplantation. This study (June 2003-January 2010) retrospectively assessed the effects of oral valganciclovir prophylaxis in adult heart transplant recipients during the first year after transplantation. Methods: In patients with normal renal function, 900 mg of oral valganciclovir was administered twice daily for 14 days after heart transplant followed by 900 mg per day for following 6 months. In the event of renal insufficiency, valganciclovir was adjusted according to the manufacturer’s recommendations. Antigenemia testing for pp65 antigen and simultaneous polymerase chain reaction (PCR) were used to document exposure to CMV. From 2003 to 2010, 146 patients (74.0% men) of mean age 50.7 ± 10.3 years at the time of heart transplant were included. Results: A total of 16 patients (11.0% of total, 75.0% male) had a positive pp65 and PCR result (ie, CMV infection) during the year following heart transplant; three of these patients had discontinued valganciclovir prophylaxis within the first 6 months following transplant because of leukopenia, including one patient developed CMV colitis. Two further patients developed CMV pneumonia during prophylactic valganciclovir therapy. Eight patients had positive pp65 and PCR tests in the 6-12 months after heart transplant following cessation of routine prophylaxis. One of these patients developed CMV pneumonia and another developed CMV colitis and CMV pneumonia. Thirty-seven of the 146 (25.3%) patients were CMV donor-seropositive/recipient-seronegative, and seven (18.9% of this subgroup) had a positive CMV test. In patients who were CMV donor-seropositive/recipient-seronegative, the risk of a positive CMV test (ie, CMV infection) was significantly elevated (P = 0.023). Conclusion: CMV prophylaxis with oral valganciclovir for 6 months following heart transplant is clinically feasible. In line with previous studies, CMV donor-seropositive/recipient-seronegative patients have a significantly elevated risk of CMV infection. In patients who prematurely discontinue valganciclovir, close monitoring of CMV antigenemia appears warranted. No significantly elevated rate of CMV infection was observed after 6 months of valganciclovir prophylaxis.
Gesehen am 06.06.2018